Green Investment Strategies In Sustainable Islamic Economics: A Viable Solution For Global Recession Challenges - Syaichoni, Ahmad (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The main objective of this study is to examine the suitability and sustainability of investment strategies, in a country's economy as a tool to face the challenges posed by the global recession. To achieve this, the researchers created a literature review of green investment's economic concepts and principles and their impact on the environment and economy. Our analysis also considered investment instruments that align with Islamic economic principles, including green sukuk and investments in renewable energy. We qualitatively analyzed the collected data to understand how implementing these strategies within economics could impact sustainability, social justice, and environmental responsibility. The findings indicate that integrating investment strategies into the economy holds significant potential for positive environmental and economic outcomes. By utilizing instruments such, as sukuk and investing in energy projects Islamic economics can foster sustainability while also addressing the challenges brought about by global recessions. Furthermore, our research delved deeply into examining how Islamic economic principles relate to the concept of investment. The global economy has suffered from recessions, but we found that adopting investment approaches can help revive it. Our research suggests that green investment strategies within the Islamic economy could be an effective and lasting solution to our global economy's challenges. Policymakers and market participants should take note and consider this strategy to maintain environmental stability while overcoming the effects of the recession.